Pengaruh Viral Marketing, Brand Ambassador dan Tagline Terhadap Keputusan Pembelian Produk Avoskin Beauty di Denpasar - Nyoman Sri Manik Parasari; Gede Crisna Wijaya; Delina Putri Purwandari; Gusi Putu Lestara Permana (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The purpose of this study was to determine the effect of viral marketing, brand ambassadors, and taglines on purchasing decisions for Avoskin beauty products in Denpasar. The type of data in this study was quantitative with a sampling technique using purposive sampling, 70 respondents who were consumers of Avoskin beauty products in Denpasar were analyzed through multiple linear regression analysis. The results obtained through the t-test show that partially viral marketing, brand ambassadors, and taglines have a positive and significant influence on purchasing decisions. The results of the study through the F test also show the effect of viral marketing, brand ambassadors, and taglines on purchasing decisions simultaneously. This shows that the better the viral marketing is done, the better the celebrity’s ability as a brand ambassador, and the better the tagline message delivered, higher the consumer purchasing decision in buying Avoskin beauty products. Keywords: Viral Marketing, Brand Ambassador, Tagline, Purchase Decision